Detection of wound healing disorders after major amputations by measurements of the microcirculation: A prospective single-center study - Zetzmann, Katharina; Papatheodorou, Nikolaos; Rühl, Eva; Yagshyyev, Shatlyk; Haney, Briain; Moosmann, Oxana; Li, Yi; Meyer, Alexander; Knieling, Ferdinand; Behrendt, Christian Alexander; Lang, Werner; Rother, Ulrich (SAGE Open Medicine, 2024)
Introduction: Although major amputations can often be avoided due to evolving methods of endovascular and surgical revascularizations techniques, in patients with chronic limb-threatening ischemia, it is still necessary in some cases. Aim of this study was the detection of wound healing disorders through intraoperative microcirculation measurements in major limb amputations. Materials and methods: In this single-center clinical study, patients with an indication for major amputation were enrolled prospectively. Cause of amputation, patients’ comorbidities including cardiovascular risk profile were assessed. Macrocirculation, as well as microcirculation were assessed. Microcirculation measurements were performed by fluorescence angiography with the administration of indocyanine green. A preoperative measurement was obtained at the amputation level, followed by three additional measurements of the amputation stump postoperatively. Wound healing was monitored and correlated with the microcirculatory findings, based on the perfusion parameters ingress and ingress rate, calculated in the indocyanine green fluorescence video sequences of the amputation stumps. Results: Forty-five patients were enrolled, including 19 (42%) below-the-knee amputations and 26 (58%) above-the-knee amputations. When considering the need for revision, a change in the microperfusion parameters was observed postoperatively. The mean value for ingress was significantly lower directly postoperatively in stumps requiring revisions (5 ± 0 A.U. versus 40.5 ± 42.5 A.U., p < 0.001). The mean value of ingress rate behaved similarly (0.15 ± 0.07 A.U./s versus 2.8 ± 5.0 A.U./s, p = 0.005). The evaluation of indocyanine green measurements when wound healing disorders occurred also showed nonsignificant differences in the mean values. Conclusion: Fluorescence angiography after major lower limb amputations appears to be an option of depicting microperfusion. Especially, the early postoperative detection of reduced perfusion can indicate a subsequent need for revision. Therefore, this method could possibly serve as a tool for intraoperative quality control after major limb amputation.
CRIS-Team Scopus Importer:2024-08-02
Keywords: fluorescence angiography; indocyanine green; Major limb amputation; microperfusion; wound healing

Intermittent negative pressure therapy in patients with no-option chronic limb-threatening ischemia - Yagshyyev, Shatlyk; Hausmann, Philipp; Li, Yi; Kempf, Julius; Zetzmann, Katharina; Dessi, Katia; Moosmann, Oxana; Almási-Sperling, Veronika; Meyer, Alexander; Gerken, Andreas L.H.; Lang, Werner; Rother, Ulrich (Vasa-Journal of Vascular Diseases, 2023)
Background: Aim of this study was to assess the influence of intermitted negative pressure (INP) therapy on the foot microcirculation in patients with no-option CLTI. Patients and methods: CLTI patients defined as no option for revascularization on the basis of an interdisciplinary vascular board decision (interventional radiology, vascular surgery) were included in this study. INP therapy was performed at home. Therapy regime was: 1 hour twice daily. Follow-up was after 6 weeks and 3 months. Microcirculation measurement was performed by laser Doppler flowmetry and white light spectrometry (oxygen to see, O2CTM). Following parameters were evaluated: oxygen saturation (sO2 in%), relative hemoglobin (rHb) and flow (in arbitrary units A.U.). Additionally the clinical outcome of the patients was assessed. Results: From September 2020 to June 2022, 228 patients were screened. In total 19 patients (13 men, 6 women, mean age was 73.95 years) were included. 6 weeks after INP therapy the microcirculation showed a significant improvement for the parameter sO2 (%) (p=0.004). After 3 months a non-significant decrease compared to 6 weeks follow-up was seen for the parameter sO2; however, the perfusion was still improved compared to baseline measurement. With regard to the microperfusion values flow (AU) and hemoglobin (AU), the changes were not significant. Clinically, the patients reported a significant reduction of rest pain after therapy (p=0.005). Conclusions: INP therapy in no-option CLTI patients showed a significant improvement of the skin perfusion after 6 weeks. Therefore, INP therapy might have therapeutic potential in these critical ill patients.
CRIS-Team Scopus Importer:2023-11-17
Keywords: chronic limb-threating ischemia; FlowOx; intermittent negative pressure; microperfusion; no-option patients; oxygen to see (O2C)